Separating underwater ambient noise from flow noise recorded on stereo acoustic tags attached to marine mammals: - Benda-Beckmann, A.M. von; Wensveen, P.J.; Samarra, F.I.P.; Beerens, S.P.; Miller, P.J.O. (2016)
Sound-recording acoustic tags attached to marine animals are commonly used in behavioural studies. Measuring ambient noise is of interest to efforts to understand responses of marine mammals to anthropogenic underwater sound, or to assess their communication space. Noise of water flowing around the tag reflects the speed of the animal, but hinders ambient noise measurement. Here, we describe a correlation-based method for stereo acoustic tags to separate the relative contributions of flow and ambient noise. The uncorrelated part of the noise measured in digital acoustic recording tag (DTAG) recordings related well to swim speed of a humpback whale (Megaptera novaeangliae), thus providing a robust measure of flow noise over a wide frequency bandwidth. By removing measurements affected by flow noise, consistent ambient noise estimates were made for two killer whales (Orcinus orca) with DTAGs attached simultaneously. The method is applicable to any multi-channel acoustic tag, enabling application to a wide range of marine species.